UTILIZATION OF EFFECTIVE MICROORGANISMS IN THE COMPOSTING PROCESS - Paredes Filho, M. V.; Florentino, L. A. (Revista Brasileira de Engenharia de Biossistemas, 2016)
This present study had as aimed to evaluate the reduction of the period of composting and the influence of the use of effective microorganisms in compost quality of the organic compound. The work was developed in the composting plant called Nuriorg Manufacture of Organic Fertilizers LTDA, located in São Sebastião da Bela Vista, MG, from March 2013 to July 2013, which were mounted 5 windrows without EM and 5 piles with EM, where the same presented 1.5 m height 3 m in base and 100 m in length, giving a volume of 225 m3 per windrow, and added to 20 liters of EM in each windrow. The collected data were subjected to Student’s t test at the level of 5% significance to compare the averages of the obtained samples in the samples without and with EM, where the physical and chemical parameters were evaluated. Also were evaluated samples without and with EM to the biological agents and heavy metals to determine the quality of the compost produced. It is concluded that EM reduced composting period, providing fertile compost in less time and consequently lower operating costs of the composting plant.